Haemophilus influenzae Septic Abortion - Thomas L. Cherpes; Shimon Kusne; Sharon L. Hillier (Hindawi Limited, 2002)
Background: Haemophilus influenzae septic abortion is typically caused by nontypeable strains of the organism. Furthermore, nontypeable species with a special affinity for the genital tract are the most frequent isolates encountered, and an ascending vaginal or cervical infection is often the suspected route of transmission.